A novel solar PV integrated fuzzy-logic controlled UAPQC device for power quality enhancement - Rao, Lingineni Shanmukha; Sharma, Pidatala Prabhakara; Shankar, Maddiguntla Bhavani; Sakethnath, Sakila Venkata; Kumar, Govindu Bharat (International Journal of Advances in Applied Sciences, 2024)
A novel solar photovoltaics (PV) connected unified active power quality conditioner (UAPQC) device is extensively adopted for enhancing the voltage and current quality of the distribution system. In a three-phase distribution system, the proposed UAPQC mitigates both load-side and source-side allied power quality (PQ) issues. Furthermore, as part of the distributed generation (DG) system, active electricity from solar PV is injected into the grid or source when solar PV is available. In this regard, the proposed UAPQC has been operated by using a workable control method, in both PQ improvement mode and DG incorporation mode. The direct current-link (DC-link) control of the shunt voltage source inverter (VSI) utilizes the proportional-integral controller, which is not suited for the regulation of DC-link voltage at the desired level because of improper selection of gain values. In this work, an intelligent fuzzy-logic DC-link control of UAPQC evidences the intelligent knowledge base for better regulation of power-quality issues. The suggested fuzzy-logic controlled UAPQC device's performance for both PQ improvement and integration of DG is validated using the MATLAB/Simulink computing tool, and simulation findings are given with an appealing comparison analysis.